Branding Strategy and AI-Driven Content Marketing to Increase the Competitiveness of Banana Cake MSMEs in Polewali Mandar Regency - Novy NRA Mokobombang; Fadliyani Nawir; Tyanita Puti Marindah Wardhani; Indrabayu -; Elly Warni; Mukarramah Yusuf; A. Ais Prayogie Alimuddin; Muhammad Abdillah Rahmat; Arliyanti Nurdin; Herlina Anwar; Nadia Indriani Sumardi; Shalomi AE Peter; Muhammad Nashwan Indrabayu; Haerul Algifari; Ratry Mutmainnah (Faculty of Engineering UNHAS, 2026)
UMKM Bolu Pisang Rezky in Polewali Mandar, West Sulawesi Province faces challenges in market visibility and competitiveness in the digital era. The product enjoys strong local market acceptance, yet marketing relies on word-of-mouth referrals, and the existing Facebook account remains inactive. A Community Service (PKM) program